2021
DOI: 10.1136/ejhpharm-2021-002914
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of inappropriate antibiotic prescribing and management through pharmacist-led antimicrobial stewardship programmes: a meta-analysis of evidence

Abstract: Purpose This meta-analysis aims to evaluate inappropriate antibiotic prescribing in the Gulf region and determine the effect of pharmacist-led antimicrobial stewardship (AMS) programmes on reducing inappropriateness. Method Articles were searched, analysed, and quality assessed through the risk of bias (ROB) quality assessment tool to select articles with a low level of bias. In step 1, 515 articles were searched, in step 2, 2360 articles were searched, and ultimately 32 articles were included by critical anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 43 publications
0
5
0
Order By: Relevance
“…This discovery changed the course of medicine and reduced infection-related mortality [1,3,4]. However, in recent times, there have been concerns over the inappropriate prescribing patterns of the Access, Watch and Reserve (AWaRe) antibiotics which has partly contributed to the development of antimicrobial resistance (AMR) [5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…This discovery changed the course of medicine and reduced infection-related mortality [1,3,4]. However, in recent times, there have been concerns over the inappropriate prescribing patterns of the Access, Watch and Reserve (AWaRe) antibiotics which has partly contributed to the development of antimicrobial resistance (AMR) [5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…The important role of pharmacists in optimizing the selection and dosage of antimicrobial agents in ASPs has been emphasized [ 5 ]. Several meta-analyses have reported that pharmacist-driven ASPs can lead to a more appropriate prescription of antimicrobial agents [ 18 , 19 , 20 , 21 ]. However, the utility of pharmacist-driven ASPs in patients with BSI remains limited.…”
Section: Discussionmentioning
confidence: 99%
“…A study conducted in Thailand by Apisarnthanarak et al compared the group that consulted a pharmacist specializing in infectious diseases after education with the group that did not, reporting that the use of inappropriate antimicrobials and length of hospital stay was significantly reduced in the consultation group [ 35 ]. A meta-analysis on the effect of ASP led by pharmacists in the Middle East reported a significant decrease in inappropriate antimicrobial prescriptions in the group that implemented ASP (relative risk = 0.36, 95% confidence interval:0.32 - 0.39) [ 36 ].…”
Section: Core Elements Of Aspmentioning
confidence: 99%